Semantic Representations in Trilingual Episodic Memory: Evidence from Priming Category Exemplars. - Plastina, Anna Franca (Textus, 2010)
The article focuses on the concept of category exemplars in trilingualism. The results of matched pairs t-tests conducted to determine any significant between-group differences for mean scores of completely shared, partly shared and separate category-exemplars are examined. It notes that lexical processing is governed by the interdependence principle in establishing connections between the single lexical stores only at the lexical level, according to another study.